La lenta segregación de los conventos de Navarra de la dominicana Provincia de Aragón culminada en 1569. - ESPONERA CERDÁN, ALFONSO (Scripta, 2020)
Since its establishment in 1300, the Dominican Province of Aragon was configured by the convents of the Kingdoms of Aragon, Valencia, Navarra, Mallorca and the Principality of Catalonia (with the Cerdanya and Roussillon), Sardinia and Sicily. Although the conquest and incorporation of the Kingdom of Navarre into Castile was in 1512 not happened the same with the Dominican convents of Navarre, that only after several attempts of the Crown culminated its incorporation into the Province of Spain in 1569. This segregation has been a topic rarely studied by historians and is the main topic of this paper.